Assessing the outcomes of IWMI's research and interventions on irrigation management transfer - Giordano, Meredith A.; Samad, Madar; Namara, Regassa E. (International Water Management Institute, 2006)
The purpose of this paper is to summarize IIMI/IWMI's past research and interventions related to irrigation management transfer and to document, to the extent possible, the academic, policy, and technical outcomes of these efforts. The application of a range of direct and indirect measurement techniques suggests an overall positive contribution from IWMI to IMT theory and application.